DAMPAK GAYA KEPEMIMPINAN KEPALA SEKOLAH PEREMPUAN TERHADAP PENGELOALAAN KONFLIK DI SDN 18 AMPENAN - Muzakki, Muhammad; Azizah, Yupiatul; Mustari, Mohammad (Berajah Journal, 2024)
Conflict in the school environment is an unavoidable phenomenon, especially in the context of diversity of characters, needs, and expectations between students, teachers, and other related parties. This study aims to examine the influence of the collaborative leadership style of female principals in managing conflict at SDN 18 Ampenan, Mataram. Using a qualitative approach and case study design, this study involved interviews, observations, and documentation to collect data from the principal, 10 teachers, and several students. The findings show that the collaborative leadership style applied by female principals, which includes open communication, active participation, and the application of coaching and restitution triangle approaches, contributes significantly to conflict management in schools. This approach increases mutual trust, encourages collaboration, and prioritizes the restoration of relationships between conflicting parties. Despite challenges such as traditional hierarchies and time constraints, this study confirms that collaborative leadership is able to create an atmosphere that supports learning and harmony in the school environment. This study provides important insights into the effectiveness of female leadership in managing conflict and improving the quality of education in schools.